Human immunoglobulins are transported to HCMV viral envelope by viral Fc gamma receptors-dependent and independent mechanisms - Vezzani, Giacomo; Pimazzoni, Silvia; Ferranti, Rossella; Calò, Stefano; Monda, Giuseppina; Amendola, Diego; Frigimelica, Elisabetta; Maione, Domenico; Cortese, Mirko; Merola, Marcello (Frontiers in Microbiology, 2023)
Human cytomegaloviruses (HCMVs) employ many different mechanisms to escape and subvert the host immune system, including expression of the viral IgG Fcγ receptors (vFcγRs) RL11 (gp34), RL12 (gp95), RL13 (gpRL13), and UL119 (gp68) gene products. The role of vFcγRs in HCMV pathogenesis has been reported to operate in infected cells by interfering with IgG-mediated effector functions. We found that gp34 and gp68 are envelope proteins that bind and internalize human IgGs on the surface of infected cells. Internalized IgGs are then transported on the envelope of viral particles in a vFcR-dependent mechanism. This mechanism is also responsible for the incorporation on the virions of the anti-gH neutralizing antibody MSL-109. Intriguingly, we show that gp68 is responsible for MSL-109 incorporation, but it is dispensable for other anti-HCMV antibodies that do not need this function to be transported on mature virions. HCMV-infected cells grown in presence of anti-HCMV monoclonal antibodies generate a viral progeny still infective and possible to be neutralized. This is the first example of a virus carrying neutralizing IgGs on its surface and their possible role is discussed.